(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Among different causes of acquired tracheal stenosis, endotracheal intubation is the commonest one. Though usually occurs after prolonged intubation or tracheostomy, tracheal stenosis may even develop following short duration of intubation. Patients commonly present with cough, wheeze, breathlessness and stridor which often mimics bronchial asthma, hence leads to a delay in diagnosis, as features may appear months to year after the procedure or even patients may remain undiagnosed especially when history is misleading. In this report we present a 28-year-old lady having an untold history of endotracheal intubation with asthma-like features who was getting treatment accordingly. With a gradually deteriorating clinical condition, she underwent our consultation. Repeated history, review of previous medical records, and necessary investigations made us establishing the confirmatory diagnosis. Prompt intervention relieved her symptoms. J Bangladesh Coll Phys Surg 2021; 39(3): 205-208